18x-15(x-3)=10(x+2)

Simple and best practice solution for 18x-15(x-3)=10(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x-15(x-3)=10(x+2) equation:


18x-15(x-3)=10(x+2)

We simplify the equation to the form, which is simple to understand
18x-15(x-3)=10(x+2)

Reorder the terms in parentheses
18x+(-15x+45)=10*(x+2)

Remove unnecessary parentheses
+18x-15x+45=+10+*(+x+2+)

Reorder the terms in parentheses
18x-15x+45=+(+10x+20)

Remove unnecessary parentheses
+18x-15x+45=+10x+20

We move all terms containing x to the left and all other terms to the right.
+18x-15x-10x=+20-45

We simplify left and right side of the equation.
-7x=-25

We divide both sides of the equation by -7 to get x.
x=3.57142857143

See similar equations:

| -5(2x+7)=-3-6x | | 4b+2(3b-8)=-25+7b | | 2x-1/6=3x-2/4 | | 5+9+4+6=0191 | | 4x^2-16y-7= | | 5(6+2x)=20 | | 8(x-2)+2=6x+2(-5+x) | | 7*a-2*5-2*6*a+5= | | x^2+7x+10=(x+5)(x+2) | | 5y-7=2y+11 | | 4+8+4+2=4396 | | 4+3+9+6=5482 | | .40x+.90(600)=.60(800+x) | | x^4+2x^3+3x^2+x+2=0 | | 6(2x-7)+6=12x-36 | | 39-5x=13x+19 | | -a^2+20a-60=0 | | 25x^2+10x+1=7 | | 16x^2-8x+1=11 | | x=4y*1.2 | | x^2-6x+9=9 | | 34=10+4q | | 5s^2+23s+24=0 | | -2X^2+14X+196=0 | | a+a=a | | 2q+2=-12 | | 4x^2+28X=240 | | 2x-4=x+9 | | (x-2)(3x+8)=0 | | ln(x)+ln(x-6)=ln(16) | | (50-4y)+(25-2x)=100 | | -36+2w=8w+w |

Equations solver categories